Pencegahan Stunting Melalui Pelatihan Pembuatan Sirup Kayu Secang dan Jeruk Sambal Kepada Ibu PKK Desa Pal IX, Kalimantan Barat - Sari, Dina Yuspita; Widyasari, Ratna (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Desa Pal IX is one of the villages in Kecamatan Sungai Kakap, Kubu Raya Regency which is affected by stunting cases with a stunting case percentage of around 12.7 percent. Sappan wood and limau citrus contain micronutrient compounds in the form of bioactive phenolic compounds and flavonoids, as well as macronutrients in the form of fats and carbohydrates. The aim of implementing this PkM is to provide education and training in making syrup from processed sappan wood and limau citrus as a macro and micro nutrient intake for handling stunting cases in Pal IX village. In general, the stages and planned activities that carried out at this PkM are preparation for activities, implementation of activities, monitoring and evaluation. The method used is the material explanation followed by training on making syrup and how to pack it to produce syrup. The results obtained are processed syrup products from sappan wood and limau citrus. In addition, there was an increase in the average score before and after the workshop, namely an increase in knowledge from a score of 30 to 68.4. Meanwhile, the results of the activity evaluation gave an index value of 86.5%, in the very satisfied category. The workshop activities were able to provide education and skills for PKK organisation in Pal IX Village in recognizing the potential of processed sappan wood and limau citrus syrup in preventing and treating stunting and making syrup product that is rich in macro-micro nutrients.